m+11=20

Simple and best practice solution for m+11=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+11=20 equation:


Simplifying
m + 11 = 20

Reorder the terms:
11 + m = 20

Solving
11 + m = 20

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + m = 20 + -11

Combine like terms: 11 + -11 = 0
0 + m = 20 + -11
m = 20 + -11

Combine like terms: 20 + -11 = 9
m = 9

Simplifying
m = 9

See similar equations:

| 8x+6x=10 | | 4x-14*3=x+7*3 | | 2m-7=8-3 | | (7x+26)+(10x-25)=138 | | 15/x=90/7 | | .14x+26=.71x-22 | | 4w+1w+3w-7= | | 15/x=7/90 | | log(33-3x^3)=2log(5-x) | | 3(x-(3-2x)+5)=5(x+4) | | 13x-14=0 | | 6(x-2)-4(x+3)=0 | | 2(x-1)-3(x-2)+4(x-3)=0 | | 4/9=24/3x-6 | | -16-7n=-21n^2+3n | | 63+5y-20=15y-13-2y | | (7b-7)-2(3b+2)=-6 | | 5y+n=m | | -3.9x-1=-3.5x+3 | | 3/4n-(-16)=28 | | 29xy-3x= | | 2(2x-2)-2(3-4z)=4 | | x=2.857142857+0.1428571429y | | 6k^2-48k=-42 | | -.75x+11=-130 | | 7(4x+8)=-224 | | 13(7c-1)-18=89c+13 | | -p^2+6p+9=0 | | F(X)=(X+2)*2-3 | | 2(3)+y=-12 | | h(2h-1)=91 | | x/-5=1-(-7) |

Equations solver categories